Shared Vulnerability, Collaborative Composition, and the Interrogation and Reification of Oppressive Values in a High School LGBTQ-Themed Literature Course. (September 2018) - Blackburn, Mollie V.; Schey, Ryan
With recent decades showing an increase in educational literacy scholarship attending to Lesbian, Gay, Bisexual, Trans, and Queer (LGBTQ) people and texts with LGBTQ themes, we sought to extend this scholarship through examining collaborative composition for public audiences beyond a classroom and school. We explored these composing practices through our ethnographically informed qualitative study of a semester-long LGBTQ-themed literature course for high school juniors and seniors, which we cotaught and coresearched. Ultimately, we found, through collaborative composing for public audiences, students and teachers in the LGBTQ-themed literature course had opportunities for interrogating oppressive values. When students and teachers shared vulnerability in that they shared responsibility for oppressive values, they embraced these opportunities. However, when students and teachers failed to share vulnerability but, instead, imposed it on a single individual, they squandered these opportunities. These findings underscore the importance of sharing vulnerability when working to interrogate oppressive values through collaborative composition for public audiences.